Challenges and Future Prospects of Electric Vehicles Using Hybrid Energy in Bangladesh - A Case Study - Aziz, Tareq; Dodaev, Zohar Al; Hossain, Md. Taufiq; Khan, Md. Yakub Ali (Peneliti Teknologi Teknik Indonesia, 2024)
The main objective of this paper is to review the current challenges and prospects of Electric Vehicles based hybrid energy in Bangladesh. Electric cars (EVs) are a viable way to lessen transportation's negative environmental effects and wean us from fossil fuels. EV adoption has a lot of promise in Bangladesh, where environmental sustainability and energy security are major concerns. However, there are a few obstacles to the general adoption of EVs, including limited infrastructure, high upfront prices, and range anxiety. The difficulties and potential benefits of EVs using hybrid energy in Bangladesh are examined in this case study. It has been reviewed the infrastructure's preparedness, present level of EV adoption, and main obstacles for implementation. In addition, it has been suggested tactics to address these issues, such as public awareness campaigns, infrastructure development, and regulatory changes. It is considered to look at how hybrid energy systems, which combine traditional power grids and renewable energy sources, can power EVs and improve energy sustainability. Bangladesh can achieve sustainable transportation goals, decrease greenhouse gas emissions, and expedite the shift to electric mobility by utilizing hybrid energy solutions and tackling systemic issues. Policymakers, industry stakeholders, and scholars can use this case study to gain important insights into how Bangladesh's energy transition and EV adoption are changing.